Circulating Cell-Free Nucleic Acids as Epigenetic Biomarkers in Precision Medicine - Rahat, Beenish; Ali, Taqveema; Sapehia, Divika; Mahajan, Aatish; Kaur, Jyotdeep (Frontiers in Genetics, 2020)
The circulating cell-free nucleic acids (ccfNAs) are a mixture of single or double-stranded nucleic acids, released into the blood plasma/serum by different tissues via apoptosis, necrosis, and secretions. Under healthy conditions, ccfNAs originate from the hematopoietic system, whereas under various clinical scenarios the concomitant tissues release ccfNAs into the bloodstream. These ccfNAs include DNA, RNA, miRNA, lncRNA, fetal DNA/RNA, mitochondrial DNA/RNA and act as potential biomarkers in various clinical conditions. These are associated with different epigenetic modifications, which show disease-related variations and so find their role as epigenetic biomarkers in clinical settings. This field has recently emerged as the latest advance in precision medicine because of its clinical relevance in diagnostic, prognostic, and predictive values. DNA methylation detected in ccfDNA has been widely used in personalized clinical diagnosis, further, there is also the emerging role of ccfRNAs like miRNA and lncRNA as epigenetic biomarkers. This review focuses on the novel approaches for exploring ccfNAs as epigenetic biomarkers in personalized clinical diagnosis and prognosis, their potential as therapeutic targets and disease progression monitors and reveals the tremendous potential that epigenetic biomarkers present to improve precision medicine. We explore the latest techniques for both quantitative and qualitative detection of epigenetic modifications in ccfNAs. The data on epigenetic modifications on ccfNAs are complex and often milieu-specific posing challenges for its understanding. Artificial intelligence and deep networks are the novel approaches for decoding complex data and providing insight into the decision-making in precision medicine.